Critical issues in genotoxicity assessment of TiO2 nanoparticles by human peripheral blood mononuclear cells. Issue 12 (4th June 2018) - Andreoli, Cristina; Leter, Giorgio; De Berardis, Barbara; Degan, Paolo; De Angelis, Isabella; Pacchierotti, Francesca; Crebelli, Riccardo; Barone, Flavia; Zijno, Andrea
Abstract: In the last years, a number of in vitro studies have been performed to assess the genotoxic activity of titanium dioxide (TiO2 ). To resolve the contradictory results, in this study, we investigated the genotoxic activity of commercial TiO2 nanoparticles (NPs) and microparticles of different forms (anatase, rutile and mix of both). We evaluated micronucleus formation in stimulated lymphocytes, as well as DNA strand breaks and 8‐oxo‐7, 8‐dihydro‐2′‐deoxyguanosine in peripheral blood mononuclear cells (PBMCs), a mixed population of lymphocytes and monocytes. Different responses to TiO2 exposure were obtained depending on the assay. Both TiO2 NPs and microparticles and all the crystalline forms elicited a significant increase in 8‐oxo‐7, 8‐dihydro‐2′‐deoxyguanosine and DNA strand breaks in the whole PBMC population, without a concurrent increase of micronuclei in proliferating lymphocytes. The distribution of DNA damage in PBMCs, detected by the comet assay, that measures DNA damage at level of single cells, indicated the presence of a more susceptible cell subpopulation. The measurement of side scatter signals by flow cytometry highlighted the preferential physical interaction of TiO2 particles with monocytes that also displayed higher reactive oxygen species generation, providing a mechanistic explanation for the different responses observed in genotoxicity assays with PBMCs and lymphocytes. This study confirmed the suitability of human PBMCs as multi‐cell model to investigate NP‐induced DNA damage, but suggested some caution in the use of stimulated lymphocytes for the assessment of NP clastogenicity. Abstract : In this study, critical issues in nanoparticle genotoxicity assessment using human peripheral blood mononuclear cells (PBMCs) were addressed. Different responses to TiO2 exposure were obtained evaluating micronucleus formation in stimulated lymphocytes and DNA strand breaks and 8‐oxo‐7, 8‐dihydro‐2′‐deoxyguanosine in PBMCs. Measurements of side and forward scatter signals by flow cytometry, highlighting a preferential physical interaction of TiO2 particles with monocytes, together with higher reactive oxygen species generation, provided a mechanistic explanation for the different responses observed between PBMCs and lymphocytes, suggesting caution when using stimulated lymphocytes for NP clastogenicity assessment.